Examining Information Technology Acceptance by Individual Professionals - Darsono, Licen Indahwati (Gadjah Mada International Journal of Business, 2005)
The mixed results of information technology (IT) investment have made the investigation of user acceptance of IT increasingly challenging. A growing body of research in user acceptance of IT literature has limited focus on individual professionals as target users. Therefore, this research investigates how external variables, namely individual differences and system characteristics influence lecturers as individual professionals to accept the internet technology. Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) are used as the main reference in this research. Findings of this research indicate that individual differences (computer self-efficacy, knowledge of search domain) and system characteristics (terminology, screen design, relevance) have indirect impact through perceived ease of use, perceived usefulness, and attitude on lecturersâ intention to use the internet. Specifically, computer self-efficacy and screen design have direct and indirect impact on intention. One issue concerning with the explanatory power of the proposed research model, which is based on TAM and TPB, compared to the rival model, which is called extended TAM, is also analyzed.